Autologous Granulocyte Colony‐Stimulating Factor‐Mobilized Peripheral Blood CD34 Positive Cell Transplantation for Hemodialysis Patients with Critical Limb Ischemia: A Prospective Phase II Clinical Trial. (30th July 2018) - Ohtake, Takayasu; Mochida, Yasuhiro; Ishioka, Kunihiro; Oka, Machiko; Maesato, Kyoko; Moriya, Hidekazu; Hidaka, Sumi; Higashide, Satoshi; Ioji, Tetsuya; Fujita, Yasuyuki; Kawamoto, Atsuhiko; Fukushima, Masanori; et al.
Abstract : Abstract: Critical limb ischemia (CLI) is a devastating disease in patients undergoing hemodialysis (HD). Based on the unsatisfactory results of autologous mononuclear cell transplantation for patients with CLI undergoing HD, we conducted a phase II clinical trial to evaluate the safety and efficacy of granulocyte colony‐stimulating factor (G‐CSF)‐mobilized peripheral blood‐derived autologous purified CD34 positive (CD34+) cell transplantation for CLI in patients undergoing HD. Six patients with CLI (two with Rutherford category 4 and four with Rutherford category 5) were enrolled. As for primary endpoint, there were no major adverse events related to this therapy. As for efficacy, the amputation‐free survival rate was 100% at 1 year after cell therapy. Both rest pain scale and ulcer size were significantly improved as early as 4 weeks after therapy compared with baseline ( p < .01), and three out of five ulcers completely healed within 12 weeks after cell transplantation. Clinical severity, including Fontaine scale and Rutherford category, significantly improved at 24 weeks after cell transplantation ( p < .05), and further improved at 52 weeks ( p < .01) compared with baseline. The improvement rate from CLI stage to non‐CLI stage was 83.3% at 52 weeks. Toe skin perfusion pressure and absolute claudication distance were also significantly improved. In conclusion, G‐CSF‐mobilized peripheral blood CD34+ cell transplantation was safe, feasible, and effective for patients with CLI undergoing HD.Stem Cells Translational Medicine 2018;7:774–782 Abstract : Outcome of autologous granulocyte colony‐stimulating factor‐mobilized CD34 positive cell transplantation for critical limb ischemia (CLI) patients on hemodialysis. Amputation‐free survival rate and CLI‐free rate at 52 weeks after cell therapy were 100% and 83.3%, respectively.